2013
DOI: 10.3109/00016489.2013.773405
|View full text |Cite
|
Sign up to set email alerts
|

Gene silencing with siRNA targeting E6/E7 as a therapeutic intervention against head and neck cancer-containing HPV16 cell lines

Abstract: E6 and E7 oncogenes of HPV16 were down-regulated by E6 and/or E7 targeting siRNAs, respectively. The expression of p53 and pRb proteins in both the E6 siRNA group and E7 siRNA group was up-regulated compared with those of control groups. The cellular proliferation and apoptosis indexes of E6 and/or E7 siRNA groups were higher than those of controls. In vivo studies showed significant inhibitory effect of E6 and/or E7 siRNA compared with those of control groups, which was consistent with in vitro studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…To expand our findings into the in vivo setting, two xenograft models using HNSCC cell lines (SCC47 and Tu212) were established as previously described (32, 33). Mice were randomly assigned to six treatment groups: PBS control, cetuximab (C), MM-121.LD, MM121.HD, Comb.LD, and Comb.HD and were treated twice a week through intraperitoneal injection.…”
Section: Resultsmentioning
confidence: 99%
“…To expand our findings into the in vivo setting, two xenograft models using HNSCC cell lines (SCC47 and Tu212) were established as previously described (32, 33). Mice were randomly assigned to six treatment groups: PBS control, cetuximab (C), MM-121.LD, MM121.HD, Comb.LD, and Comb.HD and were treated twice a week through intraperitoneal injection.…”
Section: Resultsmentioning
confidence: 99%
“…E6 associates with E6AP to mediate p53 ubiquitination and degradation, contributing to laryngocarcinoma formation. On the other hand, they are the potential targets for laryngocarcinoma therapy [ 59 , 60 ]. Our results showed that triptolide suppresses both E6 and E6AP expression, and inhibits the interaction between p53 with E6 and E6AP, resulting in the decrease of the ubiquitinated p53 level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, E6 and E7 mediate protection against interferons and elicit inappropriate or reduced activation of antigen-presenting cells (7). E6-and E7-mediated inhibition of the host's immune system underlies the effects of the related disease (11)(12)(13)(14).…”
Section: Luteolin Induces Intrinsic Apoptosis Via Inhibition Of E6/e7mentioning
confidence: 99%